Rarely Recognized Antibody Diversification in Covid-19 Evolution to Counteract Advanced SARS-CoV-2 Evasion Strategies, and Implications for Prophylactic Treatment - Mueller, Siguna (Frontiers in Physiology, 2021)
The ongoing Covid-19 pandemic underscores the importance of finding effective and safe ways to combat the virus, and to optimally understand the immune response elicited upon natural infection. This likely involves all components of the immune system, both innate and adaptive. The impetus for the rapid development of prophylactic treatment options has led to an intense focus on neutralizing antibodies (Abs), and many novel and specialized platforms have been designed to achieve that goal. B-cell immunity relies on the generation of a diverse repertoire of Abs. Their structural variation is defined in terms of amino acid composition that is encoded in the genome or acquired through somatic mutations. Yet, key examples of frequently neglected antibody diversification mechanisms involving post-translational modifications such as N- or O- linked glycosylation are present in significant portions of the population. During the last few years, these and other beyond gene sequence determined humoral immune response mechanisms have in some specific cases revealed their potent immunomodulatory effects. Nonetheless, such more unusual mechanisms have not received much attention in the context of SARS-CoV-2. Thus, with specific focus on the latter, this paper presents, (1) the rationale for considering beyond sequence determined strategies, (2) evidence for their possible involvement in Covid19 disease evolution, (3) consequences for vaccine design exemplified by one of the vaccine candidates that is currently undergoing trial, and (4) more general implications. Based on a critical interpretation of published literature, the hypotheses developed in this study point to a crucial role of non-genetic antibody diversification mechanisms in disease evolution to counteract unique immunogenicity determinants of SARS-CoV-2 infection. The involvement of post translational mechanisms may also help explain the widely varied immune response observed, not only among different patient groups, but also in terms of their observed incompatibility with SARS-CoV-2 infection in several human cell types. The article highlights potentials and challenges of these refined humoral immune response mechanisms to most optimally target non-genetic viral evasion strategies.